Revision of the lichen genus Bryoria in Belarus. II. Bryoria implexa s. l - Tsurykau, Andrei H.; Golubkov, Vladimir V.; Bely, Pavel N.; Bolsun, Iryna M. (Experimental Biology and Biotechnology, 2023)
A revision using thin-layer chromatography of the available herbarium material of the lichen genus Bryoria collected on the territory of Belarus in 1924 –2018 was carried out. Noted that the B. implexa s. l. group is represented by species B. capillaris, B. implexa s. str., B. kuemmerleana and B. vrangiana. The article provides morphological description of the species B. implexa s. str., B. kuemmerleana and B. vrangiana. Their chemical composition, ecology and data on distribution within the republic are indicated. Species B. kuemmerleana and B. vrangiana are reported for the first time for the territory of Belarus.
Keywords: biodiversity; distribution; ecology; secondary metabolites; Implexae section